Plan de importación de monofilamentos de PVC [canto] al mercado colombiano para la empresa Industrias Dismadekor. (2022)
This project was born as an initiative to generate a tool to help the growth and strengthening of the company Industrias Dismadekor through the importation of one of its main raw materials, fundamental for the finishing of its final products, with the above it is intended to generate an impact on the production costs, also that they can know the stages of the import process, the requirements and costs incurred.